Odpowiedzi

2009-11-11T20:40:11+01:00
30a²b
_______ ×2b-(3a+a×2ab²) =
5

30a²b
_______ ×2b-3a -a×2ab² =
5


30a²b
_______ ×2b-3a - 2a²b² = (30a²b ×2b-3a - 2a²b²) :5 = (60a²b² - 3a
5

- 2a²b²) :5 = (58a²b² - 3a) : 5



PS. Znak ":" zastępuje kreskę ułamkową .
2009-11-11T20:42:19+01:00
(30a²b / 5) * 2b - (3a + a * 2ab²) = 60a²b²/5 - 3a - 2a²b² =
= 60a²b²/5 - 15a/5 - 10a²b²/5 = 50a²b²/5 - 15a/5 = 10a²b² -3a

Chyba tak to będzie :|
2009-11-11T20:44:34+01:00
60a²b²
=_______ -(3a + 2a²b²)=
5
=12a²b²-3a-2a²b²= (12-2)a²b²-3a = 10a²b² - 3a

to jest pod kreska na poczatku chybaaa dobrze...